The impact of EU-ETS on the global marine industry and the relevant investment dispute resolutions - Wang, Wei; Zou, Yasha; Cheng, Yu; Liu, Yu (Frontiers in Marine Science, 2024)
Emission trading is an efficient measure to combat climate change, which is one of the biggest threats to the international community and human health. The shipping industry has previously been considered an energy-saving industry but the growth rate of its emissions far exceeds that of other industries. On 10 May 2023, the EU enacted Regulation (EU) 2023/957, which officially included the shipping industry in the EU-ETS. Therefore, this may lead to investor-state disputes regarding emission trading in the marine industry due to the conflicts between the obligation to combat climate change and the obligation to protect investments of the host states. This has resulted in the breaching of International Investment Agreements. In this context, this study aimed to propose practical recommendations for global marine market practitioners to avoid the potential risks of disputes by reflecting on the existing practice regarding climate change-related investor-state dispute resolutions and identifying the trends and problems of the current dispute resolution mechanism. These included inconsistency in the review standard, inconsistency in the review scope, and broad interpretation by the tribunal. Finally, this study proposed that by setting public purpose and exception clauses in the preambles of the International Investment Agreements and incorporating the specific obligations of the foreign investors and the regulatory power of the hosting states in the drafting stage, the potential risks for disputes regarding the new EU directive in the global marine industry could be effectively reduced.